(untitled) (AYUSHDHARA, 2023)
Eyes are the most essential and delicate organ of the human body and they need special care. Vernal Keratoconjunctivitis (VKC) is recurrent, bilateral, interstitial, self-limiting allergic inflammation of the conjunctiva having periodic seasonal incidence, also known as Warm weather conjunctivitis or Spring Catarrh. Vernal Keratoconjunctivitis (VKC) is an allergic eye disease that especially affects young boys. Aim: To study the role and efficacy of Shigrupatra Arka Ashchyotana in Kaphaja Abhishyanda. Objectives: 1. To compare the efficacy between Shigrupatra Arka Ashchyotana and olopatadine eye drop (0.1%). 2. To establish a relation between Kaphaja Abhishyanda and Vernal Kerato-Conjunctivitis (VKC). Material and Methods: 40 patients of Kaphaja Abhishyanda were randomly assigned to two groups for a clinical trial. Result: The clinical data shows that the effect of therapy on Kaphaja Abhishyanda is 73.36% in Group A and 71.79% in Group B. Conclusion: It can be concluded that clinically Shigru Patra arka Aschyotana is effective in managing the symptoms of Kaphaja Abhishyanda.